Hubungan antara Meaningful Work dan Work Engagement pada Karyawan di Fakultas Psikologi Unjani - Endah Andriani Pratiwi; Devy Sekar Ayu Ningrum; Tri Rhindra Mayang Sari (Humanitas (Jurnal Psikologi), 2021)
This study aims to determine meaningful work and work engagement of employees of the Faculty of Psychology. All employees in the organization are expected to have a sense of attachment to work and also with the organization. The method used in this research is correlational. Subjects in this study were 60 employees of the Faculty of Psychology, General Achmad Yani University (UNJANI) consisting of 25 teaching staff and 35 educational staff. The measuring instrument used in this study is to modify the measuring instrument from The Work and Meaning Inventory from Steger et al (2012) and the Utrecht Work Engagement Scale - 17 made by Scaufeli and Bakker (2003). Spearman's correlation test showed a correlation result of 0.647 (r = 0.647, p <.001), which means that there is a significant positive relationship between meaningful work and work engagement among employees at the Faculty of Psychology, Unjani. Keywords : Meaningful Work, University, Work Engagement, Employee